The Association of Diet With High Phosphatemic Index With Odds of Nonalcoholic Fatty Liver Disease - Mitra Kazemi Jahromi; Mostafa Norouzzadeh; Farshad Teymoori; Niloufar Saber; Hamid Ahmadirad; Hossein Farhadnejad; Ammar Salehi-Sahlabadi; Parvin Mirmiran (International Journal of Clinical Practice)
Conclusions: Our results suggested that a diet with a higher PI score may contribute to an increase in the odds of NAFLD independent of common confounders.